Proposed new interior design schemes for smart car showroom at No: 39, Jalan Maarof, 59100 Bangsar Kuala Lumpur / Mohd Alizulfikar Batus Shah Dollah - Dollah, Mohd Alizulfikar Batus Shah (Faculty of Architecture, Planning and Surveying, 2008)
The main objectives of this project is to proposed a new interior design scheme for SMART car showroom as a part of its under one roof marketing vehicle in Malaysia and to develop a new design scheme that would express its corporate identity as well as a well-established in an automotive industry in Malaysia and also to promote a new brand product related to a new lifestyle for its economically stability at Malaysia. Furthermore, it is also a challenge to design a car showroom which tried to explore a new method in displaying cars with an out the box approach with a new image related to a new concept itself. This project also will help to offers a comprehensive range of facilities and professional services which are rendered according to the guideline set up by the client. In conjunction of overall research and reference from better understanding, I be able to conclude with the intention of this project, it is important to create a space which fulfill the requirement and adapting appropriate design concept and scheme in order to enhance the success of design objective itself without neglecting the space that is compelling and inviting based from the importance function of building itself In conclusion, as a new brand vehicle perhaps this research will be able to be reference as a commercial item and to cater for the public as well especially for automotive vehicle. It also as a advantage for Malaysia economically stability for better to attract outside dealer for sales product mechanism. All the specified design will stately hesitate according the guideline of SMART car product.